Flavonoids, Potential Bioactive Compounds, and Non-Shivering Thermogenesis - Kang, Hye Won (Nutrients, 2018)
Obesity results from the body having either high energy intake or low energy expenditure. Based on this energy equation, scientists have focused on increasing energy expenditure to prevent abnormal fat accumulation. Activating the human thermogenic system that regulates body temperature, particularly non-shivering thermogenesis in either brown or white adipose tissue, has been suggested as a promising solution to increase energy expenditure. Together with the increasing interest in understanding the mechanism by which plant-derived dietary compounds prevent obesity, flavonoids were recently shown to have the potential to regulate non-shivering thermogenesis. In this article, we review the latest research on flavonoid derivatives that increase energy expenditure through non-shivering thermogenesis.